2016
DOI: 10.1037/com0000022
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the scalar property of timing with possums (Trichosurus vulpecula).

Abstract: Many diverse species have demonstrated interval timing, the ability to respond appropriately to time in the range of seconds to minutes, suggesting that an ability to time is adaptive. The peak procedure is a common method of studying interval time perception. In the peak procedure, animals experience a mix of fixed-interval (FI) and extinction (EXT) trials. On EXT trials, responding typically increases to a peak at the time the FI schedule would normally deliver reinforcers before decreasing. Responding on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…An increasing number of animals have been found to have some kind of number skill, whether numerosity, counting, sequencing or something similar (Bar-Shai et al 2011;Garland & Low 2014;Petrazzini et al 2015Petrazzini et al , 2017Tello Ramos et al 2015), and while most investigation into timing ability is still undertaken in pigeons and rats (e.g. Smith et al 2017), possums Trichosurus vulpecula and long-tailed bats, Glossophaga soricina, are now included in the list of species that are able to time intervals (Toelch & Winter 2013;Sargisson et al 2016).…”
Section: The Mechanistic Basis Of Cognitionmentioning
confidence: 99%
“…An increasing number of animals have been found to have some kind of number skill, whether numerosity, counting, sequencing or something similar (Bar-Shai et al 2011;Garland & Low 2014;Petrazzini et al 2015Petrazzini et al , 2017Tello Ramos et al 2015), and while most investigation into timing ability is still undertaken in pigeons and rats (e.g. Smith et al 2017), possums Trichosurus vulpecula and long-tailed bats, Glossophaga soricina, are now included in the list of species that are able to time intervals (Toelch & Winter 2013;Sargisson et al 2016).…”
Section: The Mechanistic Basis Of Cognitionmentioning
confidence: 99%
“…Russell and Burke (2016) conducted five experiments that demonstrated conditional samedifferent learning in a short-beaked echidna. Sargisson, Lockhart, McEwan, and Bizo (2016) reported that the scalar property-a psychophysical feature of respondingoccurred in brushtail possums' lever pressing for food in a peak-interval procedure. Each of these reports is an example of T0 behavior analysis because the studies used experimentally controlled settings, abstract or unfamiliar stimuli, and convenient reinforcers.…”
Section: T4mentioning
confidence: 99%
“…Time perception is a fundamental cognitive ability and has been demonstrated in a variety of species, including rats (e.g., [4,5]), pigeons (e.g., [6,7,8]), fish (e.g., [9,10]), mice, (e.g., [11]) and possums [12]. The ability to time events and adapt to temporal change in one’s environment has considerable value to the survivability of an individual [13,14], and it has been argued that timing is critical to multiple aspects of sensation, perception, and behavior, and that different neurological structures are implicated in different aspects of timing [15].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that dogs were able to perform the task and produce timing performance when tested with durations intermediate the training stimuli. The dogs performed similarly to rats [5], monkeys [33], and other animals [12,26].…”
Section: Introductionmentioning
confidence: 99%